APLIKASI PEMBELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) UNTUK SISWA SMA BERBASIS MULTIMEDIA (Information Technology and Telematics, 2013)
The development of science and technology is so rapid has made a very big change impacting nearly covers the entire human life, one of them in the field of education. As for the goal to be achieved from this research is to create a learning application software of computer and information technology (ICT) for HIGH SCHOOL students based on multimedia. This learning application created using Adobe Flash CS3 Professional which had been designed by using storyboards. These applications are tailored to the book Standard electronics (BSE) which was published by the Ministry of national education Perbukuan Center that helps teachers visualize lessons in information and communication technology (ICT) the present high school.  Keyword - Multimedia, high school, Standard electronic book (BSE), computer and information technology (ICT)